Influenza surveillance during 2015/2016 season in Portugal - Guiomar, Raquel (2017)
During 2015/2016 season the influenza activity was low and the epidemic period occurred between week 1/2015 and 9/2016 with a maximum of 59.4 ILI cases per 105 inhabitants in week 3/2015.No impact on mortality for all causes was observed in any age group. The influenza A(H1)pdm09 was predominant (94% of flu confirmed cases). Influenza B/ Victoria was identified sporadically (4% of flu cases) in late season. Situation that contrasts with European influenza picture, that showed a late peak of influenza B/ Victoria. Other respiratory viruses were detected in influenza negative cases, rhinovirus and coronavirus in higher frequencies. The antigenic and genetic analysis of circulating influenza A(H1)pdm09 showed similarity with vaccine strain. The majority of influenza B virus belonged to Victoria lineage and clade 1A, dissimilar from 2015/16 vaccine strain. Although few A(H3) viruses in circulation, almost all AH3 viruses were similar to strain recommended for next winter vaccine. Low influenza activity level can be linked with a higher influenza activity in last season and exceptional climatic conditions during the winter (higher temperature than usual). Predominance of A(H1)pdm09 and circulation of B/Victoria, recorded in all age groups, is in line with 2015 serosurvey that showed lower levels of seroprotection for these viruses comparing to A(H3) and B/Yamagata lineage.